Parents' support in the sports career of young gymnasts - Nunomura, Myrian; Oliveira, Mauricio Santos (My University, 2013)
From the very first moment of entrance in sports up to the time of their successful achievements, parents have a pronounced influence on the sport's career of their children. This influence is readily seen when the parent's dedicated involvement and investment, both emotional and financial, put into the support they give to their children in sports is taken into account. This is all done with the objective that their young athlete may stay involved and reach their full potential. To describe the parental support in the context of Brazilian Artistic Gymnastics in formative categories, this study addressed the perceptions that young gymnasts have toward the behavior and attitude of their parents through a field research conducted among 29 sport institutions involving a total of 163 athletes. We have found that parental support enabled and greatly influenced the child's entering into sports, their access to the practice of a sport, their level of participation, their degree of involvement, and their physical and emotional wellbeing. Moreover, the parental support is crucial to the commitment and dedication of the young gymnast. However, when this support is perceived in a negative way it can result in stress, conflicts between parents and children, burnout and may provoke dropout.
Keywords: Artistic gymnastics; Parents; Youth sports